2008
DOI: 10.1586/17434440.5.5.567
|View full text |Cite
|
Sign up to set email alerts
|

Results using the AO hook plate for dislocations of the acromioclavicular joint

Abstract: The AO Hook plate has been used for stabilization of acromioclavicular joint dislocations. We present our experience of this newly introduced device in a general hospital, since there are not many papers in the literature reporting on this. A total of 16 patients were treated with the AO Hook plate between November 2001 and November 2003 at Princess Alexandra Hospital in Harlow, UK. For functional assessment 6 months after removal of the plate, the constant score and the pain visual analogue score were used. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 27 publications
1
33
0
3
Order By: Relevance
“…The hook plate is one of the most commonly used implants for acute ACJ dislocations with good clinical and biomechanical results. 20,21) Koukakis et al 9) reported that the use of hook plate results in excellent functional outcome for the treatment of ACJ dislocations and it is suitable for inexperienced surgeons. Unlike the previously used Wolter plate, hook plates do not require drilling into the acromion and is a relatively less challenging surgical technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hook plate is one of the most commonly used implants for acute ACJ dislocations with good clinical and biomechanical results. 20,21) Koukakis et al 9) reported that the use of hook plate results in excellent functional outcome for the treatment of ACJ dislocations and it is suitable for inexperienced surgeons. Unlike the previously used Wolter plate, hook plates do not require drilling into the acromion and is a relatively less challenging surgical technique.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the previously used Wolter plate, hook plates do not require drilling into the acromion and is a relatively less challenging surgical technique. 9,22) Recently, locking plates shaped as conventional hook plates but with locking screws are being commonly used, and good results are being reported. [6][7][8] An advantage of the hook plate is the relatively easy implantation procedure and early postoperative mobilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the technique's disadvantage is evident-it requires a second operation to remove the implant. Furthermore, this technique was usually associated with some complications, such as shoulder pain, subacromial impingement, loosening and unhooking of the plate, limited postoperative range of motion (especially abduction of the shoulder) and fractures distal to the plate [12,18].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][15][16][17][18] The use of AO hook plates in the treatment of dislocations is simpler and takes less time than the use of Wolter plates. In fact, Koukakis et al 19) have reported that successful treatment of acromioclavicular joint dislocation using AO hook plates is possible even if surgeons are not familiar with such cases, given they are aware of the basics of plate fixation. Henkel et al 2) carried out surgery using AO hook locking plates in ligament repair on 19 patients, of which 90% returned to work and resumed normal physical activity.…”
Section: Discussionmentioning
confidence: 99%